Upaya Peningkatan Mobilitas Fisik Pada Keluarga Tn. WDengan Stroke Hemoragik Di Sukoharjo - Suryaningtiyas, Fatma Dewi, H.M. Abi Mullisir.,S.KM.,M.Kep (2016)
ABSTRACT Stroke is a media problem that it is still be the second cause of the ilness and death in Europe and the third cause in America. As much as 10% stroke patient have the weakness that needs a treatment. The cause of stroke is hemorrhaging in the brain of thrombosis and embolism. Blood lump will go into bloodstream as the result of another disease or there is a closed injury in the part of brain that it also clogs the arteri of the brain. As a result, the function of brain breaks off and declines. The number of stroke patients in Indonesia significantly increases. Indonesia is currently the most country with a very large number of stroke patients in Asia. This scientific paper is written by the writer using a descriptive method in the case study approach. It is a scientific method that consist of submitting the data, analysing the data, and making a conclusion of the data. Taking a case on March, 29th - April, 2 rad 2016 in combongan village around Sukoharjo health centre, it is used to write this scientific paper. In obtaining the data, the writer uses some methods, such as: an interview, an observation, a pysical examination, and studying documents from some journals and books. Supporting with some journals that have themes related to give nursing care which had done by the writer. A hospital sheet from Mrs. S teels that she began to feel sick after she came to her causin party and she ate lamb meats even though she has been detected having hypertension before, it called high blood pressure. In that time, Mrs. S couldn't speak clearly so she should be hospitalized. In the hospital, she got a treatment for 11 days. To know be representation of nursing care for haemorrhagic stroke patient, it consists of a assesment, an intervension, an implementation, and a nursing evaluasion. Those are used by a method with doing the process of nursing care to a haemorrhagic stroke patient. After doing a nursing care for three times to visit, the problem of physical mobility disorder is partially resolved. Keywords: Stroke, rupture, embolism, thrombosis